Correlation between Saliva Levels and Serum Levels of Free Uremic Toxins in Healthy Volunteers - Nicolas Fabresse; Islam Amine Larabi; Emuri Abe; Elodie Lamy; Claire Rigothier; Ziad A. Massy; Jean-Claude Alvarez (Toxins, 2023)
The objective of the present study was to investigate the putative correlation between the saliva concentration and free serum concentration for 10 uremic toxins (UTs; eight protein-bound solutes: 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF), hippuric acid (HA), indole-3-acetic acid (3-IAA), indoxyl sulfate (I3S), kynurenic acid (KA), kynurenine (KYN), p-cresyl glucuronide (pCG), and p-cresyl sulfate (pCS); two free, water-soluble, low-molecular weight solutes: phenylacetylglutamine (PAGN) and trimethylamine N-oxide (TMAO); and three precursors: tyrosine (Tyr), phenylalanine, and tryptophan). Saliva samples and blood samples were collected simultaneously from 18 healthy volunteers. After the addition of internal standards, 50 µL of saliva or serum were precipitated with methanol. UTs and precursors were quantified using a validated LC-MS/MS method. The saliva–serum correlation was statistically significant (according to Spearman’s coefficient) for six UTs (TMAO, HA, I3S, pCS, 3-IAA, and CMPF). Tyr presented a weak saliva-serum correlation (p = 0.08), whereas the other two precursors did not show a saliva–serum correlation. For three UTs (KYN, KA and pCG), we were unable to test the correlation since the saliva or serum levels were too low in many of the volunteers. The present study is the first to report on the saliva concentrations of TMAO, KYN, HA, PAGN, pCG, and 3-IAA.